2020
DOI: 10.1051/0004-6361/202039145
|View full text |Cite
|
Sign up to set email alerts
|

Separation between RR Lyrae and type II Cepheids and their importance for a distance determination: the case of omega Cen

Abstract: The separation between RR Lyrae (RRLs) and type II Cepheid (T2Cs) variables based on their period is debated. Both types of variable stars are distance indicators, and we aim to promote the use of T2Cs as distance indicators in synergy with RRLs. We adopted new and existing optical and near-infrared (NIR) photometry of ω Cen to investigate several diagnostics (color-magnitude diagram, Bailey diagram, Fourier decomposition of the light curve, and amplitude ratios) for their empirical separation. We found that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 115 publications
(157 reference statements)
2
21
0
Order By: Relevance
“…We therefore do not yet have a wellcalibrated PL relation for Galactic ACEP stars, and too few have been studied so far with TESS (Clementini et al 2019;Plachy et al 2021). The importance of distance determination was also highlighted by Braga et al (2020), who showed that short-period ACEP and Type II Cepheids can overlap in period with long-period RR Lyrae stars. Period itself is therefore not a unique classifier, and a reliable separation of Galactic short-period ACEP stars from long-period RR Lyrae stars will require accurate light curve shape information, distances and colors.…”
Section: Anomalous Cepheid Candidatesmentioning
confidence: 99%
“…We therefore do not yet have a wellcalibrated PL relation for Galactic ACEP stars, and too few have been studied so far with TESS (Clementini et al 2019;Plachy et al 2021). The importance of distance determination was also highlighted by Braga et al (2020), who showed that short-period ACEP and Type II Cepheids can overlap in period with long-period RR Lyrae stars. Period itself is therefore not a unique classifier, and a reliable separation of Galactic short-period ACEP stars from long-period RR Lyrae stars will require accurate light curve shape information, distances and colors.…”
Section: Anomalous Cepheid Candidatesmentioning
confidence: 99%
“…We did not find any correlation of the residuals of PLRs with metallicity for T2Cs, implying a negligible dependence on metallicity. Braga et al [97] used T2C PLRs in ω Cen to obtain a distance to the cluster that is consistent with independent methods, including those based on RRL stars. Since T2Cs and RRL follow the same PLRs in NIR bands, their combined PLRs can be used as an alternative to classical Cepheids for providing the calibration of the first rung of the extragalactic distance scale.…”
Section: Period-luminosity Relationsmentioning
confidence: 82%
“…Even though NGC 6441 is metal-rich, previous studies of its RRab have shown that they have periodamplitude diagrams similar to those in OoII GCs [96]. Braga et al [97] showed that the long-period RRab in ω Cen follows the locus of OoIII RRab, similar to NGC 6441 variables. Rich et al [98] first discovered that metal-rich NGC 6441 and NGC 6388 not only have expected red HB but also blue HB components that extend through the IS.…”
Section: The Bailey Diagrams and The Oosterhoff Dichotomymentioning
confidence: 89%
See 2 more Smart Citations